Analysis of Risk Factors Associated with the Incidence of ARI in Children Under Five in the Work Area of the Surisina Health Center, Ngada Regency - Emirensiana Luweng; Mustakim Sahdan; Ribka Limbu (Lontar : Journal of Community Health, 2023)
Acute Respiratory Infection (ARI) is an acute respiratory disease caused by an infectious agent transmitted from humans, which attacks the throat, nose, and lungs which lasts approximately 14 days. Acute respiratory infections are caused by various factors, namely age, nutritional status, low birth weight, history of exclusive breastfeeding, research status, smoking habits, ventilation, and occupancy density. This study aims to analyze the factors associated with the incidence of acute respiratory infections in children under five in the working area of the Surisina Health Center. This type of research is an analytic survey using a case-control study design. The population in this study were all toddlers in the working area of the Surisina Public Health Center, Ngada Regency which accommodated 504 toddlers, the sample size was 108 toddlers with a 1:1 division, namely 54 cases and 54 controls. Data was collected by using interview, observation, and measurement techniques on 108 toddlers obtained by simple random sampling technique. The results showed that there was a significant relationship between the history of exclusive breastfeeding (p-value = 0.000), nutritional status (p-value = 0.016), smoking habits (p-value = 0.009), residential density (p-value = 0.020), age (p-value = 0.005). There was no significant relationship between exercise status (p-value = 0.715), ventilation (p-value = 0.254). It is hoped that the community, especially mothers of toddlers, will pay more attention to the living environment, nutritional status, exclusive breastfeeding, and smoking habits.